A PSYCHOANALYTIC OVERVIEW OF SUICIDE IN ADOLESCENCE (Isagoge - Journal of Humanities and Social Sciences, 2022)
In the present article we explore some authors who investigate suicide among adolescents and trace, as a hypothesis of its occurrence, the lack of subjective constitution of this group. The purpose of the study is to seek to understand, from the elucidation of adolescence and the mourning of this phase, suicide in its social conception and Werther effect. With reference to legal issues and official data about the practice of suicide by adolescents, we explored hypotheses that could lead to the interruption of this path full of challenges.
Keywords: Suicide; Adolescent; Psychoanalysis